Pattern-Reconfigurable Antenna With Switchable Wideband to Frequency-Agile Bandpass/Bandstop Filtering Operation - Seyed-Ali Malakooti; Christophe Fumeaux (IEEE Access, 2019)
A three-element antenna system with the ability to operate in a unique set of switchable and frequency-tunable configurations is presented here. Firstly, this antenna system can switch between sum and difference radiation patterns using a mirrored arrangement of antenna feeding lines that bypasses the need for an additional phase inverter. Secondly, the frequency response of this antenna can be switched between three states of operation, namely wideband, tunable bandpass, and tunable bandstop characteristics. Importantly, the pattern reconfigurability function can be generated in all three states of the frequency-agile response. To realize this extended set of selectable functionalities, a three-state filter and a switchable power divider are used to feed a triple-element quasi-Yagi-Uda antenna array. The proposed system is experimentally validated, demonstrating sum and difference patterns over a measured 79.8% fractional bandwidth for the wideband state of operation, and a tunability of 51.3% for the bandpass state and 50.3% for the bandstop state.